Lights, camera, cook! - Harper, Charise Mericle (Next Best Junior Chef, 2017)
Follows Tate, Rae, Caroline, and Oliver, ages nine to eleven, both on and off-camera as they compete in a televised cooking competition. Includes cooking tips.